Duane retraction syndrome characterized by inner ear agenesis and neurodevelopmental phenotype in an Italian family with a variant in MAFB. Issue 3 (28th December 2021) - Pascolini, Giulia; Passarelli, Chiara; Lipari, Martina; Chandramouli, Balasubramanian; Chillemi, Giovanni; Di Giosaffatte, Niccolo'; Novelli, Antonio; Grammatico, Paola
Abstract :